Sosialisasi Pencegahan Perilaku Bullying pada Siswa Kelas VI SD Negeri Hatalai, Kota Ambon - Ronald Darlly Hukubun; Marlin Chrisye Wattimena; Laury Marcia Ch. Huwae; Charlota Masully (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
The activities carried out are anticipating bullying behavior. Because bullying can have a negative impact on the development of children in elementary schools, this is a current concern. One of the many things that may cause someone to bully another is the perpetrator's belief that his or her actions do not fall into a certain category. The problem at Hatalai State Elementary School is children's ignorance and lack of focus on bullying. To overcome this, an anti-bullying outreach program was created which aims to educate Hatalai State Elementary School students about bullying. This socialization process consists of three parts: (1) preparation, namely creating activity schedules, resources and activity plans. (2) Carrying out socialization at the implementation stage (3) assessment stage by explaining shortcomings and successes after socialization. Socialization was also provided. The implementation results show that students can understand the information included in the anti-bullying socialization program at Hatalai State Elementary School. The program covers topics such as verbal, physical, social, cyber bullying and how to deal with it.